An analytic cross-sectional study to explore the role of TNF-α level as a marker for diabetic polyneuropathy - Debarati Chanda; Aditi Aikat; Saswati Ray; Sangita Sen; Debjani Chakraborti (Asian Journal of Medical Sciences, 2022)
Background: Diabetes has reached epidemic proportion in India. The most common complication of Type 2 diabetes mellitus (T2DM) is diabetic polyneuropathy (DPN). Various theories have been proposed to explain development of DPN, among which newer concepts are activation of inflammatory pathways. Aims and Objectives: The aim of the study was to determine the relationship between tumor necrosis factor alpha (TNF-α) levels and painless and painful variants of DPN in T2DM patients. Materials and Methods: The study was carried out on 57 subjects. The subjects were divided into four groups; Group 1 had 15 healthy controls without diabetes; Group 2 had 12 control group patients of T2DM without neuropathy; 20 patients of T2DM with painful neuropathy were included in Group 3 and 10 T2DM patients with painless neuropathy. TNF-α level was measured by drawing 5 ml blood from individual patients using Ray Bio Human TNF-α enzyme-linked immunoassay kit. Results: Plasma TNF-α level increases from non-diabetic control (221.7±46.91 pg/ml) to diabetic control (743.6±87.27 pg/ml) and also further increased in painful neuropathy patients (1343±283.8 pg/ml). Interestingly, TNF-α was found to be significantly decreased (441.4±118.3 pg/ml) in patients with painless neuropathy. Conclusion: TNF-α level increased in diabetic neuropathy but did not correlate with severity of neuropathy.